Family Functioning and its Relationship with Emotional Regulation in Adolescents from Ambato City - Tobar Viera, Andrea; Lara Machado, Rosario (Revista Ecos de la Academia, 2023)
The family is the bedrock of the emotional well-being of children and adolescents, and its functioning guarantees an affective balance during childhood, and a better management and regulation of emotions during adolescence. This process is understood as the capacity of the individual to adjust emotions to specific situations. The objective of the study is to determine the relationship between family functioning and emotional regulation in adolescents. The research methodology had a quantitative approach, with a descriptive design of correlational scope, non-experimental, cross-sectional with a sample of 460 adolescents from 12 to 17 years old. Two questionnaires were used: the FF-SIL to assess family functioning and the ERQ-CA to measure emotional regulation in adolescents. The results evidence a high level of family functioning (82.2%), showing a positive correlation (rho= 0.214***) with cognitive reassessment. In this way, it is determined that adolescents with a greater perception of family functioning have better management of their emotions in different contexts.